The West Wants In: Regionalism, Class, and Labour/Le Travail, 1976-2002 - Bright, David (Labour / Le Travail, 2002)
“The west wants in” was the rallying cry of the Reform Party launched in 1987. What the West wanted, how its aspirations could be fulfilled within Confederation, and how fulfilling them might change Canada itself came to dominate the party’s agenda over the next decade or so. The West’s relationship to the rest of the country has also been a major theme in Canadian labour history, of ten with respect to notions of “western radicalism” or “western exceptionalism.” Reviewing Labour / Le Travail’s coverage of Canadian labour over the past quarter-century, this article reviews the extent to which western workers have been represented, the varying ways in which their identity has been characterized, and the degree to which traditional perceptions of a “radical” West have been either reinforced or revised as a result.
Keywords: CLASS identity; Canada; Labor movement; REFORM Party of Canada; SOCIOLOGY literature; WESTERN countries; Working class